Controlling the greater grain borer - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Effective protection against the Greater Grain Borer can be obtained for about eight months by mixing shelled grain with permethrin dust before storing it in sacks. But storing maize on the cob and dusting it does not give protection. Unfortunately,...